Identidad personal y “ciencia del hombre” en el Tratado de la naturaleza humana de Hume. Una problematización - Gonzales LLanos, Marcia (Pontificia Universidad Católica del Perú. Instituto Riva-Agüero, 2017)
The present study aims to point out a possible inconsistency between David Hume’s account of the personal identity problem and the methodology of the philosophical project he sketches in A Treatise of Human Nature, and also to assess Nelson Pike’s defense of the Hume’s position, which is considered by many to have dissolved the problem. It will be argued that this solution turns out to be insufficient since it does not solve the explanatory gap left by the inconsistency. In order to make this visible, a reformulation of the objection based on the work of Donald Ainslie will be presented, as it is a proposal that also serves as a plausible explanation for Hume’s discredit of his own account in the Appendix.

El presente trabajo se propone señalar una posible inconsistencia entre la explicación brindada por David Hume respecto del problema de la identidad personal y la metodología del proyecto filosófico que presenta en su Tratado de la naturaleza humana, así como evaluar una defensa de la postura humeana elaborada por Nelson Pike, la cual pretende disolver el problema. Lo que se sostendrá es que dicha salida resulta insuficiente pues aún persiste el vacío explicativo detectado. Para mostrar esto, se reformulará la objeción a partir de la propuesta de Donald Ainslie, quien parece brindar un motivo plausible para explicar por qué Hume desacreditó su propio tratamiento de la identidad personal en el Apéndice.
“Personal Identity, and “Science of Man” in Hume’s Treatise. An Examination”.
Keywords: Hume; Identidad personal; Sustancia; Ciencia del hombre; Teoría del conocimiento; https://purl.org/pe-repo/ocde/ford#6.03.01